Os artefactos metálicos recolhidos no povoado calcolítico muralhado do Outeiro Redondo (Sesimbra). Estudos composicionais com recurso ao método da espetrometria de fluorescência de raios X : DOI: https://doi.org/10.5281/zenodo.7920074 - Cardoso, João Luís; Bottaini, Carlo (Estudos Arqueológicos de Oeiras, 2023)
This study is based on the analysis of copper metal alloys from 109 artifacts collected in the excavations carried out in the walled Chalcolithic settlement of Outeiro Redondo (Sesimbra) using X‑ray fluorescence and compares these results with those obtained by the same team in the walled Chalcolithic town of Leceia, about 50 km away. It was concluded that the compositions of the metallic alloys did not differ during the two phases of occupation verified of the settlement, that dates back to the end of the Early Chalcolithic and the Full/Late Chalcolithic, encompassing an interval of about 500 years. It was also concluded, based on the comparative exercise carried out with the results obtained in Leceia, and in other Chalcolithic sites in the Portuguese territory, that the presence of arsenic in the studied copper alloys assumes an occasional character, resulting from the nature of the ores used, and not from any intentional addition; in fact, it appears that the arsenic frequency curves obtained for both sites show a normal Gaussian distribution, although the average levels of arsenic in Outeiro Redondo are slightly higher than those found in Leceia. It was noted, however, the presence of higher levels of arsenic in a specific type of instrument analysed, the saws or handsaws, compared to the rest of the artifacts, both in Outeiro Redondo and in Leceia.